Cultural Elements in English Learning: English Teachers’ Perspectives - Apriliansyah Hamid; Hidayah Jumatul; Edy Sarwo (ELITE JOURNAL, 2020)
This study investigated Indonesian English teachers’ perspectives on cultural elements in English learning. 12 English teachers who had various teaching experiences were engaged as the participants of this study. They were selected to be the participants using purposive sampling technique. The data revealed that Indonesian English teachers rested upon a modernist paradigm that was anchored in the native-speakerism ideology. Philosophically and practically, they had not yet integrated the aspects of multiculturality and interculturality that are intrinsically the integral parts of English teaching and learning. The present study recommends that English teaching and learning in Indonesia be conceptualized on the basis of intercultural language teaching and learning which sets a goal leading student to manage to communicate using English with all people in the world with their diverse cultures. Further studies are expected to develop an intercultural English learning model that aligns with the anthropological nature of Indonesian students.